PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI): PERKEMBANGAN DAN TANTANGANNYA - Robert K. Sembiring (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2010)
This paper is about PMRI, the Indonesian version of realistic mathematics education developed in the Netherlands. It is a movement to reform mathematics education in Indonesia. What and why PMRI and the problems and challenges it faces in its development. It began as a small experiment ten years ago, now becomes a national movement.